2011
DOI: 10.1039/c1dt10740b
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Speciation of Nickel(ii) onto Ca-Montmorillonite: Batch, EXAFS Techniques and Modeling

Abstract: The sorption speciation of Ni(II) on Ca-montmorillonite was evaluated using a combination of batch experiments, extended X-ray absorption fine structure (EXAFS) spectroscopy and modeling. The pH and temperature at the aqueous-montmorillonite interface affects both the extent of Ni(II) sorption as well as the local atomic structure of the adsorbed Ni(II) ions. At 0.001 mol/L Ca(NO 3 ) 2 and low pH, the study reveals that the majority of Ni(II) is adsorbed in the interlayers of Ca-montmorillonite coordinated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…At high Ni(II) loadings, the formation of precipitation/co-precipitation phases on minerals might be expected [14,15]. Several macroscopic studies showed the strong Ni retention on mineral surfaces [9][10][11][12][13][14][15]. The sorption mechanisms of Ni(II) varied with different mineral surfaces and the environmental conditions, and then the desorption and migration of Ni(II) pollutant were also different.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…At high Ni(II) loadings, the formation of precipitation/co-precipitation phases on minerals might be expected [14,15]. Several macroscopic studies showed the strong Ni retention on mineral surfaces [9][10][11][12][13][14][15]. The sorption mechanisms of Ni(II) varied with different mineral surfaces and the environmental conditions, and then the desorption and migration of Ni(II) pollutant were also different.…”
Section: Introductionmentioning
confidence: 94%
“…There is no denying that the environmental condition has more or less influence on Ni(II) sorption and speciation. It was reported that the uptake mechanisms of Ni(II) onto minerals were dominated by cation exchange or outer-sphere surface complexation at low pH, and by inner-sphere surface complexation at high pH, which were dependent on the environmental conditions such as ionic strength, pH and temperature [9][10][11][12][13]. At high Ni(II) loadings, the formation of precipitation/co-precipitation phases on minerals might be expected [14,15].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The presence of Al 3+ in acidic soils and its competition for exchange sites might have resulted in reduced Ni adsorption in these soils like Cd (Cavallaro and McBride, 1978). According to Tan (2011), at low pH, majority of Ni (II) was adsorbed in the inter layers of Ca-montmorillonite co-ordianted by six water molecules in an octahedron as an outer-sphere complex; on the other hand, at higher pH, inner-sphere surface complexes are formed. Also, the Fe-oxides present in acidic soils may lead to decreased Ni adsorption by blocking access of Ni to exchange sites as reported by Cowan et al (1992) and Zachara et al (1992) for Cd.…”
Section: Resultsmentioning
confidence: 99%